Debt and financial crises - Wee Chian Koh; M. Ayhan Kose; Peter Nagle; Franziska Ohnsorge; Naotaka Sugawara (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
Emerging market and developing economies have experienced recurrent episodes of rapid debt accumulation over the past fifty years. This paper examines the consequences of debt accumulation using a three-pronged approach: an event study of debt accumulation episodes in 100 emerging market and developing economies since 1970; a series of econometric models examining the linkages between debt and the probability of financial crises; and a set of case studies of rapid debt buildup that ended in crises. The paper reports four main results. First, episodes of debt accumulation are common, with more than 500 episodes occurring since 1970. Second, around half of these episodes were associated with financial crises which typically had worse economic outcomes than those without crises- after 8 years output per capita was typically 6-10 percent lower and investment 15-22 percent weaker in crisis episodes. Third, a rapid buildup of debt, whether public or private, increased the likelihood of a financial crisis, as did a larger share of short-term external debt, higher debt service, and lower reserves cover. Fourth, countries that experienced financial crises frequently employed combinations of unsustainable fiscal, monetary and financial sector policies, and often suffered from structural and institutional weaknesses.
Keywords: E32; E61; G01; H12; H61; H63; 330; Financial crises; currency crises; debt crises; banking crises; public debt; private debt; external debt